PENGARUH MEKANISME TATA KELOLA PERUSAHAAN & MODEL BISNIS TERHADAP PENGUNGKAPAN MODAL INTELEKTUAL - Aryandra Anantama; Totok Dewayanto (Diponegoro Journal of Accounting, 2020)
The aim of this study is to examine the role of board compositions, blockholder ownership and business model on intellectual capital disclosure. This study uses firm size, leverage and return on asset as a control variable.The population in this study consists of manufacturing companies in Indonesia Stock Exchange for the period 2015 - 2017. Sample determined with purposive sampling method. Total sample of this research are 225 companies.This study used multiple regression analysis for hypotheses testing. The results of this study shows that board size, blockholder ownership and business model has positive and significant effect on intellectual capital disclosure. This study also shown that board independence has positive but insignificant effect on intellectual capital disclosure.